STUDI PENGADAAN BARANG DAN JASA PEMERINTAH BERBASIS ELEKTRONIK (E-PROCUREMENT) DALAM MEWUJUDKAN GOOD GOVERNANCE DI KABUPATEN TRENGGALEK - Santi Okta Wijayanti; Ari Subowo (Journal of Public Policy and Management Review, 2016)
This research reviews about Implementation of the Goods and Service Supply of Goverment on Based Electronic (e-Procurement) in Trenggalek Regency. This policy are formulated because many problems of the convensional goods and service supply of goverment and the rapidly of development of Information Technology. Beside that, e-procurement is one of the innovation from Public Service Government to realized Good Governance. Goals of this researched is to analyze policy implementation of e-procurement and to identify the factors supporting and inhibiting to realized Good Governance in Trenggalek Regency. Researcher analyze the supply process by applying of Good Governance principles, they are tranparency, participation, accountability, efectiveness and efficiency, responsiveness, strategic vision and equity. The factors supporting and inhibiting policy implementation based on Rondinelli and Shabbir Cheema’s teory, those are: (1) Environmental Conditions; (2) Inter-organizationship; (3) Resources for Program Implementation; and (4) Characteristic of Implementing Agencies. This reseach use qualitative descriptive design through observation, deep interview and library research. Informants from this research are employees from ULP, LPSE and supply partners. Based on the results of this study we can conclud that the policy of e-procurement policiy were implemented in Trenggalek Regency to realizing good governance have not maximied yet. Some of the factors that influence are the limited financial support, the quantity and quality of human resources and the infrastructure supporting for the implementation of e-procurement policy. Recommendations given by the researcher are need to increase the capacity of human resources in terms of both quantity and quality through education and training for employees of LPSE and application users of SPSE both committes and suppliyers,enhacement of infrastructure 2 supporting for e-procurement, financial support from the local government and enhancement of interaction or cooperation among agencies e-procurement implementing in Trenggalek Regency.